POSHAN's abstract digest on maternal and child nutrition research - Issue 28 - Avula, Rasmi (International Food Policy Research Institute, 2019)
In this issue of Abstract Digest, we present to you a collection of articles on various outcomes, determinants and interventions related to maternal and child nutrition, from around the world, with relevance to India. In addition, this issue features articles on multiple micronutrient supplementation in pregnancy from a special issue of the Annals of the New York Academy of Sciences and a systematic scoping review of food environment research in low-and middle -income countries.